2013
DOI: 10.4103/0970-9371.126652
|View full text |Cite
|
Sign up to set email alerts
|

Practical significance of utilizing fine needle aspiration cytology as an adjunct diagnostic aid in the preoperative presumptive diagnosis of ameloblastoma

Abstract: Background:Cytological reports of ameloblastoma are relatively rare in the literature. Appropriate cytologic diagnosis may play a significant role in its preoperative presumptive diagnosis, especially when incisional biopsy findings are inadequate.Aim:To systematically study the detailed cytomorphologic features of ameloblastoma and to evaluate the role of fine needle aspiration cytology (FNAC) in its preoperative diagnosis.Materials and Methods:In this study, FNAC was done on 26 cases of intra-osseous jaw les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 3 publications
(8 reference statements)
1
21
1
2
Order By: Relevance
“…From 390 studies identified after exclusion of duplicates, a total of 48 articles were considered eligible for full‐text reading, of which 40 were excluded (Appendix S2), and 8 were finally included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 390 studies identified after exclusion of duplicates, a total of 48 articles were considered eligible for full‐text reading, of which 40 were excluded (Appendix S2), and 8 were finally included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall judgment was “at risk of bias” for seven included studies, only the study of Kaliamoorthy et al was judged with an overall “low risk of bias.” Within domains assessed in the QUADAS‐2 tool, items regarding bias or applicability related to the index test and reference standard were scored as with “high” or “unclear” risk in the majority of studies. Concerns were due to lack of information or reportedly absence of blinding of personnel from histopathological analyses when performing FNAC evaluations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have shown an overall cytological diagnostic accuracy of 58.3%. However, Kaliamoorthy et al have found a sensitivity of 86.6% and specificity of 100% of FNAC in the diagnosis of ameloblastoma. In our case the peripheral palisading of the tumor cells with reversal of nuclear polarity was quite evident, which is usually difficult to appreciate on cytosmears.…”
mentioning
confidence: 98%